(untitled) (Psikologiya Journal, 2025)
Childhood trauma constitutes a major risk factor with long-term consequences for mental health and psychosocial functioning into young adulthood. This study aims to explore in depth the lived experiences of emotion regulation among young adults with histories of childhood trauma and their implications for psychological and social functioning. A qualitative approach with an interpretative phenomenological design was employed. Data were collected through semi-structured in-depth interviews with young adults aged 20–30 who had experienced childhood trauma and analyzed using thematic analysis. The findings reveal that childhood trauma shapes maladaptive emotion regulation patterns characterized by difficulties in emotional awareness, predominant use of suppression, rumination, and avoidance, and limited cognitive reappraisal capacity. These emotion regulation impairments function as a central mechanism linking childhood trauma to increased vulnerability to depression, anxiety, relational dysfunction, and reduced quality of life in young adulthood. The study underscores the importance of strengthening emotion regulation capacities through targeted psychological interventions as a core strategy for supporting psychosocial recovery among young adult survivors of childhood trauma.